2019
DOI: 10.1111/jonm.12774
|View full text |Cite
|
Sign up to set email alerts
|

Positive Impacts of Electronic hand‐off systems designs on Nurses’ communication effectiveness

Abstract: Aim Different designs of electronic hand‐off systems might have different levels of effectiveness; this study validated the effectiveness of systems with an Identify, Situation, Background, Assessment and Recommendation (ISBAR) design to one without such a design. Background Adverse consequences in hospital commonly occur when there are breakdowns in the transmission of information between team members. To ensure information accuracy and consistency, some Taiwan hospitals implemented electronic hand‐off system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The implementation of ineffective communication in handover between shifts is a major factor that contributes to unwanted events, including sentinel events that cause danger or death to patients (3) . The use of the system in transferring nurses between shifts can apparently improve the implementation of effective communication (2) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The implementation of ineffective communication in handover between shifts is a major factor that contributes to unwanted events, including sentinel events that cause danger or death to patients (3) . The use of the system in transferring nurses between shifts can apparently improve the implementation of effective communication (2) .…”
Section: Discussionmentioning
confidence: 99%
“…The quality of nursing care provided to patients depends on the ability of nurses to carry out effective communication (1) . The competence of nurses to communicate effectively can reduce errors in providing care to enable the provision of safe and quality care (2). In addition, effective communication helps patients and families to understand how their health conditions, goals and treatment plans will be provided to patients (3,4) .…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of hospital practices have confirmed that using information systems improves workflow and improves medical service quality [ 57 ]. Hou et al confirmed that nurses using an electronic handover system can improve their communication efficiency [ 58 ]. Jalali et al discovered that information systems involving drug interactions can support physicians in making decisions more efficiently [ 59 ].…”
Section: Methodsmentioning
confidence: 99%
“…The main reasons include overdependence on the individual experience of handover nurses and handover techniques, spending too much time searching for patient‐related information before handover, manual entry tasks (Burgess et al, 2020; Zhu & Mao, 2017), missing IT support, and an inability of nurses to rapidly review critical information during handover (Bukoh & Siah, 2020; Schmidt et al, 2019). This results in omitted, incomplete, erroneous, and truncated handover information, as well as other potential risk factors that are detrimental to patient safety (Bhabra et al, 2007; Hou et al, 2019). An electronic handover (e‐handover) system is a tool that uses a hospital's electronic medical records system to help physicians obtain patient‐related data (Delardes et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the design of e‐handover systems has not taken into account standardized evidence‐based handover tools. Furthermore, these systems are mostly used for patient information exchange between physicians, are rarely used by nurses, and are very rarely used in pediatrics (Alhamid et al, 2016; Delardes et al, 2020; Gordon et al, 2018; Hou et al, 2019; Vidyarthi & Coffey, 2016; Yazici et al, 2013). Thus, we developed a standardized e‐handover system that combines the extract‐load‐transform (ELT) database technology and SBAR, and we assessed the effects of implementing a standardized e‐handover system on pediatric nursing handover quality and efficiency.…”
Section: Introductionmentioning
confidence: 99%